Head Injuries in Contact Sports – Literature Review - Hoksa, Kacper; Broda, Aleksandra; Jodłowski , Krzysztof; Dubniewicz, Ewa; Majewska, Paula; Staszek, Alicja; Łoskot, Wiktoria; Matczak, Mateusz; Szwech, Jan; Jasiński, Karol (Quality in Sport, 2025)
Head injuries in athletes are an increasingly common issue, not only in professional sports but also due to the growing number of amateurs participating in contact sports. These sports include not only martial arts such as boxing, judo, or MMA but also team sports, including some of the most popular ones like soccer, rugby, American football, and hockey. The aim of this paper is to review the available literature on the frequency and mechanisms of head and neck injuries in various sports, as well as to propose possible methods for preventing these injuries and rehabilitation after they occur. The article discusses both acute and chronic injuries, as well as long-term health consequences. It highlights the need for further research in the field of biomechanics, athlete monitoring, and the development of effective health protection strategies for athletes. The article was prepared by analyzing multiple databases, including PubMed, Google Scholar, and Elsevier. Conclusions: There is also a lack of conclusive evidence on the mechanisms behind these injuries, which makes it difficult to develop programs to reduce the frequency of neurological injuries. Many years of systematic research and athlete monitoring, with detailed documentation of all injuries, are needed. Additionally, further biomechanical analyses are required to understand the forces acting on athletes and how well protective equipment performs. Only after obtaining such results it will be possible to prepare better strategies to protect the health and life of athletes in these disciplines.